2019
DOI: 10.1002/jcp.28885
|View full text |Cite
|
Sign up to set email alerts
|

High concentration magnesium inhibits extracellular matrix calcification and protects articular cartilage via Erk/autophagy pathway

Abstract: The significant cytopathological changes of osteoarthritis are chondrocyte hypertrophy, proteoglycan loss, extracellular matrix (ECM) calcification, and terminally, the replacement of cartilage by bone. Meanwhile, magnesium ion (Mg 2+ ), as the second most abundant divalent cation in the human body, has been proved to inhibit the ECM calcification of hBMSCs (human bone marrow stromal cells), hVSMCs (Human vascular smooth muscle cells), and TDSCs (tendon-derived stem cells) in vitro studies. The ATDC5 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 71 publications
3
36
0
Order By: Relevance
“…Male 3-week-old Sprague-Dawley rats were purchased from the Experimental Animal Center of Nanjing Medical University. Primary BMSCs were isolated and characterized as described previously [26,27]. Under sterile conditions, BMSCs were collected by flushing the femurs and tibias with alpha minimal essential medium (αMEM; Sigma-Aldrich CO, St. Louis, MO, USA) containing fetal bovine serum (FBS, 15%; Lonza Inc., Walkersville, MD, USA), ultraglutamine (1%, Lonza), penicillin (100 U/mL), and streptomycin (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male 3-week-old Sprague-Dawley rats were purchased from the Experimental Animal Center of Nanjing Medical University. Primary BMSCs were isolated and characterized as described previously [26,27]. Under sterile conditions, BMSCs were collected by flushing the femurs and tibias with alpha minimal essential medium (αMEM; Sigma-Aldrich CO, St. Louis, MO, USA) containing fetal bovine serum (FBS, 15%; Lonza Inc., Walkersville, MD, USA), ultraglutamine (1%, Lonza), penicillin (100 U/mL), and streptomycin (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their effects on bone formation, Mg ions at optimal concentrations enhance the phenotype of chondrocytes [46], and magnesium deficiency elevates the numbers of adipocytes [47]. High concentrations of magnesium inhibit calcification of the extracellular matrix and protect articular cartilage via the Erk/autophagy pathway [27].…”
mentioning
confidence: 99%
“…Mg deficiency in the extracellular matrix of cartilage may lead to typical joint cartilage lesions [42]. In contrast, high concentrations of IA Mg can signi cantly inhibit extracellular matrix calci cation and protect articular cartilage [44,45]. Similarly, clinical trials have found that subjects with lower levels of serum Mg had a higher prevalence of knee chondrocalcinosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, animal experiments suggest that Mg de ciency in the extracellular matrix of cartilage may lead to typical joint cartilage lesions [43]. In contrast, high concentrations of IA Mg can signi cantly inhibit extracellular matrix calci cation and protect articular cartilage [44,45]. Similarly, clinical trials have found that subjects with lower levels of serum Mg had a higher prevalence of knee chondrocalcinosis [46].…”
Section: Discussionmentioning
confidence: 99%